ESL Writing Instruction in K-12 Settings: Pedagogical Approaches and Classroom Techniques - Bhowmik, Subrata; Kim, Marcia (Language and Literacy / Langue et littératie)

(untitled) (Language and Literacy Researchers of Canada, 2022)
Writing is an important literacy skill that K-12 students must develop for academic success. For young ESL students, developing writing skills entails both learning English and developing writing as a literacy skill. The need for this dual skill development underlines the challenges of teaching K-12 ESL writing, as teachers must strike a balance between teaching writing as a tool for students’ English language development and literacy skill. This paper reports on findings related to pedagogical approaches and classroom techniques that are prevalent in K-12 ESL writing instruction. Our research is based on a systematic review of 49 studies published between 2010 and 2019. Using content analysis, three pedagogical approaches were identified: (a) approaches centered on teacher perspectives, (b) approaches centered on student perspectives, and (c) approaches centered on emerging research and theories of ESL writing instruction. As well, the analysis yielded four classroom techniques: (a) adopting SFL-oriented and genre-based activities, (b) utilizing ESL-bilingual student writers’ language learning traits, (c) incorporating digital technology, and (d) adapting instructional practices in response to student needs. Critically reflecting on these pedagogical approaches and classroom techniques, the paper discusses the advantages and challenges of implementing them in the classroom. The paper provides a taxonomy of instructional practices that K-12 ESL writing teachers may find useful.